2021
DOI: 10.3389/fmars.2021.705053
|View full text |Cite
|
Sign up to set email alerts
|

Sponge–Microbe Interactions on Coral Reefs: Multiple Evolutionary Solutions to a Complex Environment

Abstract: Marine sponges have been successful in their expansion across diverse ecological niches around the globe. Pioneering work attributed this success to both a well-developed aquiferous system that allowed for efficient filter feeding on suspended organic matter and the presence of microbial symbionts that can supplement host heterotrophic feeding with photosynthate or dissolved organic carbon. We now know that sponge-microbe interactions are host-specific, highly nuanced, and provide diverse nutritional benefits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 210 publications
1
23
0
Order By: Relevance
“…The impacts of environmental factors on sponge–microbe relationships have been addressed by several studies carried out at different latitudes, with some studies assessing the effects at different ambient, temporal, and/or geographic scales ( Anderson et al, 2010 ; Erwin et al, 2012 , 2015 ; Luter et al, 2015 ; Easson et al, 2020 ), while others tested environmental stress obtaining variable results depending on the species and also on the duration and strength of the environmental alterations ( Webster et al, 2008 ; Fan et al, 2013 ; Cárdenas et al, 2014 ; Pineda et al, 2017 ; Ramsby et al, 2018 ). Previous studies have suggested the existence of strong interactions between geographic, environmental, and host factors influencing the microbiome of some species ( Easson et al, 2020 ; Freeman et al, 2021 ). Taking into account current environmental changes occurring around the globe, it is important to better understand the sponge–microbiota patterns in terms of temporal and spatial scales as well as intra- and interspecific variations and its key ecosystem functions in order to better understand and predict potential direct and cascading effects produced by future environmental changes.…”
Section: Introductionmentioning
confidence: 99%
“…The impacts of environmental factors on sponge–microbe relationships have been addressed by several studies carried out at different latitudes, with some studies assessing the effects at different ambient, temporal, and/or geographic scales ( Anderson et al, 2010 ; Erwin et al, 2012 , 2015 ; Luter et al, 2015 ; Easson et al, 2020 ), while others tested environmental stress obtaining variable results depending on the species and also on the duration and strength of the environmental alterations ( Webster et al, 2008 ; Fan et al, 2013 ; Cárdenas et al, 2014 ; Pineda et al, 2017 ; Ramsby et al, 2018 ). Previous studies have suggested the existence of strong interactions between geographic, environmental, and host factors influencing the microbiome of some species ( Easson et al, 2020 ; Freeman et al, 2021 ). Taking into account current environmental changes occurring around the globe, it is important to better understand the sponge–microbiota patterns in terms of temporal and spatial scales as well as intra- and interspecific variations and its key ecosystem functions in order to better understand and predict potential direct and cascading effects produced by future environmental changes.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of types of low-toxic PAH, the NL type was identified in all samples. NL is a simple aromatic hydrocarbon [9,38,116]. Naphthalene-based products, such as camphor, are thought to come from household activities, for example, in products used to eradicate insects and absorb odors in bathroom toilets.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of PR in the sample is thought to have come from the transportation activities of petroleum carriers. This assumption was reinforced by the identification of the PAH type AZ, as the PAH type is a component of petroleum as are some of its derivative products, including those from coal processing [9,84,118]. This allegation is quite reasonable, because BCI operates three ports: a container port, a passenger port, and a fish-landing port.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations